2019
DOI: 10.1038/s41531-019-0090-8
|View full text |Cite
|
Sign up to set email alerts
|

Infection with mosquito-borne alphavirus induces selective loss of dopaminergic neurons, neuroinflammation and widespread protein aggregation

Abstract: Neuroinvasive infections with mosquito-borne alphaviruses such as Western equine encephalitis virus (WEEV) can cause post-encephalitic parkinsonism. To understand the mechanisms underlying these neurological effects, we examined the capacity of WEEV to induce progressive neurodegeneration in outbred CD-1 mice following non-lethal encephalitic infection. Animals were experientally infected with recombinant WEEV expressing firefly luciferase or dsRed (RFP) reporters and the extent of viral replication was contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 84 publications
0
66
0
Order By: Relevance
“…Another neurotropic virus, the mosquito-borne alphavirus, Western equine encephalitic virus (WEEV) also induces post-encephalitic parkinsonism. Like the influenza virus, WEEV induced activation of microglia and astrocytes, selective loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) and behavioral abnormalities consistent with PD in mouse models 130 . Importantly, the common denominator of these viruses is that they enter the CNS and directly infect cells.…”
Section: Covid-19 and The Possibility Of A Post-viral Parkinsonism: Cmentioning
confidence: 99%
“…Another neurotropic virus, the mosquito-borne alphavirus, Western equine encephalitic virus (WEEV) also induces post-encephalitic parkinsonism. Like the influenza virus, WEEV induced activation of microglia and astrocytes, selective loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) and behavioral abnormalities consistent with PD in mouse models 130 . Importantly, the common denominator of these viruses is that they enter the CNS and directly infect cells.…”
Section: Covid-19 and The Possibility Of A Post-viral Parkinsonism: Cmentioning
confidence: 99%
“…Given the particular sensitive phenotype of nigrostriatal DA neurons, they might be vulnerable to the release of reactive oxygen species and would be among the first cell populations to be affected. This DA neuron loss may sometimes be paralleled by aggregation of α-syn and may persist even after the infection has ceased [54]. On the other hand, if the disease process is further defined by multiple sequential hits, inhibiting LRRK2 during these events may prove most effective in protecting the already stressed DA neurons.…”
Section: Viewpoint -Is Lrrk2 Inhibition In Parkinson's Patients Suffimentioning
confidence: 99%
“…aggregation via HEN. This includes microbial surfaces (Bantle et al, 2019;Ezzat et al, 2019), lipid vesicles (Habchi et al, 2018), and nanoparticles (Linse et al, 2007). Additionally, polymer surfaces such as glycosaminoglycans (GAGs) (Iannuzzi et al, 2015) and nucleic acids (Liu and Zhang, 2011) have been shown to accelerate amyloid aggregation.…”
Section: Amyloid Nucleation Mechanismsmentioning
confidence: 99%